2018
DOI: 10.3390/cells7120251
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Remodeling in Response to Resistance Training, Anabolic Androgenic Steroids and Aging

Abstract: Exercise training (ET), anabolic androgenic steroids (AAS), and aging are potential factors that affect tendon homeostasis, particularly extracellular matrix (ECM) remodeling. The goal of this review is to aggregate findings regarding the effects of resistance training (RT), AAS, and aging on tendon homeostasis. Data were gathered from our studies regarding the impact of RT, AAS, and aging on the calcaneal tendon (CT) of rats. We demonstrated a series of detrimental effects of AAS and aging on functional and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 174 publications
(283 reference statements)
0
15
0
Order By: Relevance
“…Chronic tendon disorders, most commonly affecting the calcaneus tendon (CT), represents approximately 50% of all sports injuries (Barin et al, 2019). Moreover, CT has a relevant biomechanical function in response to RT, which justifies the choice of use CT (Guzzoni et al, 2018). The CT was immediately dissected from the posterior right paw and frozen in clean microtubes using liquid nitrogen and then stored at −80 • C. All tendons were dissected by an experienced researcher in order to prevent contamination of other tissues.…”
Section: Euthanasiamentioning
confidence: 99%
“…Chronic tendon disorders, most commonly affecting the calcaneus tendon (CT), represents approximately 50% of all sports injuries (Barin et al, 2019). Moreover, CT has a relevant biomechanical function in response to RT, which justifies the choice of use CT (Guzzoni et al, 2018). The CT was immediately dissected from the posterior right paw and frozen in clean microtubes using liquid nitrogen and then stored at −80 • C. All tendons were dissected by an experienced researcher in order to prevent contamination of other tissues.…”
Section: Euthanasiamentioning
confidence: 99%
“…Vinicius revealed that in comparison to their levels in young animals, collagen-I (Col-I) content and glucosaminoglycans (GAGs) were reduced in the calcaneal tendon of older sedentary animals, while biglycan (Bgn) and fibromodulin (Fmod) content were not altered with aging. The gene expression levels of COL-1, COL-3, Insulin-Like Growth Factor-Ia (IGF-Ia), Matrix metalloproteinase-2(MMP-2), tissue inhibitor of metalloproteinase-2(TIMP-2), and Bgn were decreased in aged tendons [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of trauma due to muscle tension is probably a confluence of numerous factors related to the MTJ's ultrastructural architecture and its contact surface 18,19 . Thus, physical training appears as an alternative to strengthen the muscle-tendon structure and ensure an effective transmission of force from the skeletal muscle to the tendon [20][21][22][23] . According to Curzi et al, MTJ plasticity seems to be related to exercise intensity 24 .…”
mentioning
confidence: 99%